Access to gender-affirming hormones during adolescence and mental health outcomes among transgender adults. - Jack L Turban; Dana King; Julia Kobe; Sari L Reisner; Alex S Keuroghlian (PLoS ONE, 2022)
Objective To examine associations between recalled access to gender-affirming hormones (GAH) during adolescence and mental health outcomes among transgender adults in the U.S. Methods We conducted a secondary analysis of the 2015 U.S. Transgender Survey, a cross-sectional non-probability sample of 27,715 transgender adults in the U.S. Using multivariable logistic regression adjusting for potential confounders, we examined associations between access to GAH during early adolescence (age 14-15), late adolescence (age 16-17), or adulthood (age ≥18) and adult mental health outcomes, with participants who desired but never accessed GAH as the reference group. Results 21,598 participants (77.9%) reported ever desiring GAH. Of these, 8,860 (41.0%) never accessed GAH, 119 (0.6%) accessed GAH in early adolescence, 362 (1.7%) accessed GAH in late adolescence, and 12,257 (56.8%) accessed GAH in adulthood. After adjusting for potential confounders, accessing GAH during early adolescence (aOR = 0.4, 95% CI = 0.2-0.6, p < .0001), late adolescence (aOR = 0.5, 95% CI = 0.4-0.7, p < .0001), or adulthood (aOR = 0.8, 95% CI = 0.7-0.8, p < .0001) was associated with lower odds of past-year suicidal ideation when compared to desiring but never accessing GAH. In post hoc analyses, access to GAH during adolescence (ages 14-17) was associated with lower odds of past-year suicidal ideation (aOR = 0.7, 95% CI = 0.6-0.9, p = .0007) when compared to accessing GAH during adulthood. Conclusion Access to GAH during adolescence and adulthood is associated with favorable mental health outcomes compared to desiring but not accessing GAH.